2016
DOI: 10.1111/ejn.13422
|View full text |Cite
|
Sign up to set email alerts
|

Blood cells serve as a source of factor‐inducing rapid ischemic tolerance in brain

Abstract: Ischemic tolerance (IT) has gained attention as an attractive strategy for improving stroke outcome. Recently, it was shown that signal responsible for rapid IT induction (tolerance induction factor - TIF) is transmitted via circulating blood. In this study, we have hypothesized about the role of the blood cell compartment in TIF production. We used hind-limb ischemia to generate TIF as a rapid preconditioning against transient middle cerebral artery occlusion (MCAO). The essential properties of protein synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Our previous findings indicate that the preserved protein synthesis (i.e . transcription and translation) in stimulated blood cells plays an essential role in neuroprotection against stroke (Bonova et al ). The implementation of the bioinformatic‐based analysis in the present experiments allowed us to identify actively secreted proteins that were extracellularly released because of stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous findings indicate that the preserved protein synthesis (i.e . transcription and translation) in stimulated blood cells plays an essential role in neuroprotection against stroke (Bonova et al ). The implementation of the bioinformatic‐based analysis in the present experiments allowed us to identify actively secreted proteins that were extracellularly released because of stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the potential of peripheral blood cells for tissue protection and repair has recently been proven. In our previous work, we demonstrated that a mixture of all peripheral blood cells can promote brain tissue protection after stimulation (Bonova and Gottlieb ; Bonova et al ). However, the main cellular component of blood, that is, erythrocytes, discard their nuclei during maturation and are thought to be unable to synthesise proteins.…”
mentioning
confidence: 95%
“…There is ample evidence that RIC-mediated neuroprotection could be transferred indirectly via blood transfusion [ 4 , 5 ] or the blood cell-derived secretome drawn from RIC-stimulated animals [ 6 ]. In our recent work, we discovered that protein synthesis is crucial for the induction of tolerant phenotype in ischaemia-affected animals.…”
Section: Introductionmentioning
confidence: 99%